2009
DOI: 10.1097/cji.0b013e31819d297e
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Patients With Metastatic Renal Cancer With Modified Vaccinia Ankara Encoding the Tumor Antigen 5T4 (TroVax) Given Alongside Interferon-α

Abstract: Approximately 90% of renal cell tumors overexpress the tumor antigen 5T4. The attenuated strain of vaccinia virus, modified vaccinia Ankara, has been engineered to express 5T4 (TroVax). We conducted an open-label phase 1/2 trial in which TroVax was administered alongside interferon-alpha (IFNalpha) to 11 patients with metastatic renal cell carcinoma. Antigen-specific cellular and humoral responses were monitored throughout the study, and clinical responses were assessed by measuring the changes in tumor burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
“…These studies showed MVA-5T4 to be well tolerated and able to induce 5T4-specific immune responses in most patients. Furthermore, associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of the nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 96%
“…In line with this assertion, IFN-a treatment has been previously observed to reduce Treg numbers in patients with melanoma or renal cell carcinoma (37,38), whereas, conversely, declining IFN-a levels and impaired IFN-a signaling in patients with cancer seem to be correlated with an increase in the number of Treg and a higher risk of cancer progression (39)(40)(41). Recent reports on improved immune responses upon co-administration of IFN-a with peptide vaccines in renal (42), pancreatic (43), and colorectal cancer (44) represent additional evidence. Numerous investigations have firmly established a key role of cAMP in the suppressive function of Treg (27)(28)(29)(30)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was well tolerated with no serious adverse events, and all patients demonstrated 5T4-specific antibody response. Overall median time to progression was longer than interferon-alpha when administered alone (Hawkins, Macdermott, Shablak, et al, 2009). …”
Section: Viral Vector-based Immunotherapymentioning
confidence: 99%